2013
DOI: 10.1016/j.jalgebra.2013.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Weak Bialgebras of fractions

Abstract: We construct the algebra of fractions of a Weak Bialgebra relative to a suitable denominator set of group-like elements that is almost central, a condition we introduce in the present article which is sufficient in order to guarantee existence of the algebra of fractions and to render it a Weak Bialgebra. The monoid of all group-like elements of a coquasi-triangular Weak Bialgebra, for example, forms a suitable set of denominators as does any monoid of central group-like elements of an arbitrary Weak Bialgebra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(30 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Later (Hopf) face algebras were integrated to weak bialgebras (weak Hopf algebras) by Böhm, Nill, and Szláchanyi [3]. Bennoun and Pfeiffer mentioned to the Hopf closure (they called the Hopf envelope) of the coquasitriangular weak bialgebra in [2]. Schauenburg [16] showed that a weak bialgebra (weak Hopf algebra) is a left bialgebroid (× R -Hopf algebra) whose base algebra is Frobenius-separable.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Later (Hopf) face algebras were integrated to weak bialgebras (weak Hopf algebras) by Böhm, Nill, and Szláchanyi [3]. Bennoun and Pfeiffer mentioned to the Hopf closure (they called the Hopf envelope) of the coquasitriangular weak bialgebra in [2]. Schauenburg [16] showed that a weak bialgebra (weak Hopf algebra) is a left bialgebroid (× R -Hopf algebra) whose base algebra is Frobenius-separable.…”
Section: Introductionmentioning
confidence: 99%
“…for all l ∈ L and a, b ∈ A. Here we write ∆ L (a) = a [1] ⊗ a [2] , called Sweedler's notation. The right-hand-side of (2.5) is well defined because of (2.3).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations